Real‐life assessment of chronic rhinosinusitis patients using mobile technology: The mySinusitisCoach project by EUFOREA. Issue 11 (19th June 2020) - Seys, Sven F.; De Bont, Shana; Fokkens, Wytske J.; Bachert, Claus; Alobid, Isam; Bernal‐Sprekelsen, Manuel; Bjermer, Leif; Callebaut, Ina; Cardell, Lars‐Olaf; Carrie, Sean; Castelnuovo, Paolo; Cathcart, Russell; et al.
Abstract: Background: Chronic rhinosinusitis (CRS) is a chronic inflammatory disease associated with a substantial personal and socioeconomic burden. Monitoring of patient‐reported outcomes by mobile technology offers the possibility to better understand real‐life burden of CRS. Methods: This study reports on the cross‐sectional evaluation of data of 626 users of mySinusitisCoach (mSC), a mobile application for CRS patients. Patient characteristics of mSC users were analysed as well as the level of disease control based on VAS global rhinosinusitis symptom score and adapted EPOS criteria. Results: The mSC cohort represents a heterogeneous group of CRS patients with a diverse pattern of major symptoms. Approximately half of patients reported nasal polyps. 47.3% of all CRS patients were uncontrolled based on evaluation of VAS global rhinosinusitis symptom score compared to 40.9% based on adapted EPOS criteria. The impact of CRS on sleep quality and daily life activities was significantly higher in uncontrolled versus well‐controlled patients. Half of patients had a history of FESS (functional endoscopic sinus surgery) and reported lower symptom severity compared to patients without a history of FESS, except for patients with a history of more than 3 procedures. Patients with a history of FESS reported higher VAS levels for impaired smell. Conclusion: Real‐life data confirm the high disease burden in uncontrolled CRS patients, clearly impacting quality of life. Sinus surgery improves patient‐reported outcomes, but not in patients with a history of more than 3 procedures. Mobile technology opens a new era of real‐life monitoring, supporting the evolution of care towards precision medicine. Abstract : This study reports on the cross‐sectional evaluation of patient‐reported outcome measures in 626 chronic rhinosinusitis patients of which half reported nasal polyp disease. Over 40% of patients were uncontrolled, which clearly impacted their quality of life. Sinus surgery improved patient‐reported outcomes, but not in patients with a history of more than 3 procedures. Abbreviations: CRSw/sNP, chronic rhinosinusitis with/without nasal polyps; FESS, functional endoscopic sinus surgery; VAS, visual analogue scale.